Simulacros enunciativos e efeitos de blindagem no discurso humorístico - Valério, Yvantelmack Dantas (2018)
The main purpose of this doctoral thesis is to describe, in the light of the French Semiotics, Greimasian, the shielding effect, understood here as a protection against the identification of the subject-humorist with a specific axiological universe, produced by humorous discourse. For this, we start from a conception of enunciation as a presupposed instance of the utterance which, as such, can only be described or reconstructed by the marks left in the utterance. As an implication of this conception of enunciation, we also try to describe the enunciative and communicative procedures that would characterize an identity dynamics, an enunciative procedure, therefore, what we call the subject-humorist. It is evident that our purpose is not to identify an empirical subject, but rather a discursive mode of operation that we think involves enunciative strategies, shifting out and shifting in; ambiguity of the communicative, fiduciary and veridictory agreement; and also the modes of interaction mobilized by the humorous statement. Since our object, the shield, does not lend itself to a numerically quantifiable analysis, we adopted a qualitative methodology. Through this path, we select texts recognized as humorous that assume the role of exemplifying our reflections about the phenomenon of shielding. The results of our analyzes showed that the shielding effect occurs as the mobilized enunciative procedures and the established communicative agreements empty the subject-humorist semantically, create enunciative instances with different degrees of depth and preclude the attribution to the subject-humorist of the conjunction or disjunction of the values updated by the statement.